2017
DOI: 10.14411/fp.2017.016
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of proteolytic enzymes by Eubothrium rugosum (Cestoda) from the gut of burbot Lota lota

Abstract: Parasitic organisms inhabiting the alimentary canal should permanently resist the destructive action of host digestive enzymes. The intestinal parasites were shown to produce specific protease inhibitors protecting them from proteolysis. However, little is known about this adaptive mechanism in cestodes so far, especially for the tapeworms dwelling inside the fish intestines. Here, we explored the ability to inactivate proteolytic enzymes in the fish tapeworm Eubothrium rugosum (Batsch, 1786) (Bothriocephalide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…Therefore, the tapeworm body apparently contains no substances responsible for inhibition of the host digestive proteinases. Thus, the data obtained show that it is possible to use the whole worms for similar studies, which proves the validity of the basic conclusions from some previous works that were made using the extracts of the homogenized worms (Izvekova et al, 2017a).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Therefore, the tapeworm body apparently contains no substances responsible for inhibition of the host digestive proteinases. Thus, the data obtained show that it is possible to use the whole worms for similar studies, which proves the validity of the basic conclusions from some previous works that were made using the extracts of the homogenized worms (Izvekova et al, 2017a).…”
Section: Discussionsupporting
confidence: 82%
“…Previously, we found that the extracts from E. rugosum cestodes have an inhibitory effect on trypsin activity, as well as on the proteolytic activity of homogenized intestinal mucosa from its host fish, the burbot (Izvekova et al, 2017a). In the present study, we tried to determine whether the incubation medium of this tapeworm has an inhibitory ability and whether this ability is associated with the brush border of the worm or with its body.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In order to inhabit the fish gut, tapeworms possess different features that facilitate their ability to survive under specific conditions of the fish gut. Thus, cestodes are characterized by specific surface epithelium or, tegument, associated with feeding processes and parasite protection from the host enzymes (inhibition of host proteinase activity) (Izvekova, Frolova, & Izvekov, ). It was shown that cestodes, as a component of intestinal communities, can also impact digestive processes and be an important factor that effect on the fish gut microbiota (Izvekova, ; Izvekova & Korneva, ).…”
Section: Introductionmentioning
confidence: 99%